2016
DOI: 10.1007/s11481-016-9666-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers of Simian Immunodeficiency Virus Encephalitis

Abstract: Antiretroviral therapy has led to increased survival of HIV-infected patients but also increased prevalence of HIV-associated neurocognitive disorders. We previously identified YKL40 as a potential cerebrospinal fluid (CSF) biomarker of lentiviral central nervous system (CNS) disease in HIV-infected patients and in the macaque model of HIV encephalitis. The aim of this study was to define the specificity and sensitivity along with the predictive value of YKL40 as a biomarker of encephalitis and to assess its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Although CSF NFL, GFAP, and YKL-40 levels were not significantly different between PWH with or without asymptomatic CSF viral escape, CSF YKL-40 correlated positively with CSF IL-1β, IFN-γ, IP-10, and NFL and negatively with neurocognitive T scores. Previous studies have suggested that CSF YKL-40 is associated with increased plasma and CSF HIV/SIV RNA, HIV/SIV encephalitis, and markers of axonal injury [ 19 , 21 , 22 , 48 , 51 , 52 ]. CSF YKL-40 is a biomarker of glial activation associated with neuroinflammation [ 19 , 21 , 53 ] that is produced by CNS macrophages, microglia, and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although CSF NFL, GFAP, and YKL-40 levels were not significantly different between PWH with or without asymptomatic CSF viral escape, CSF YKL-40 correlated positively with CSF IL-1β, IFN-γ, IP-10, and NFL and negatively with neurocognitive T scores. Previous studies have suggested that CSF YKL-40 is associated with increased plasma and CSF HIV/SIV RNA, HIV/SIV encephalitis, and markers of axonal injury [ 19 , 21 , 22 , 48 , 51 , 52 ]. CSF YKL-40 is a biomarker of glial activation associated with neuroinflammation [ 19 , 21 , 53 ] that is produced by CNS macrophages, microglia, and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the potential utility of CSF YKL-40 as a predictive marker for encephalitis, as retrospective analysis of serial CSF samples revealed a YKL-40 increase occurring two to eight weeks prior to the manifestation of clinical symptoms in affected animals. Moreover, it is believed that the initiation of YKL-40 production within the central nervous system (CNS) occurs in astrocytes [77]. In another study involving BRP-39-deficient mice, these animals exhibited more severe clinical scores in experimental autoimmune encephalitis (EAE) and displayed heightened neuroinflammation and gliosis compared to their wild-type counterparts.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Thus, CSF neopterin is considered a very specific biomarker of inflammation in the CNS compared to the periphery. Another marker of CSF neuronal damage is human cartilage glycoprotein 39 (YKL-40) produced by microglia following SIV infection [ 72 , 73 , 74 ]. YKL-40 is upregulated in the CSF of SIV-infected pigtailed macaques that develop encephalitis and correlates with an increase of viral load in CSF [ 74 ], while macaques that do not develop encephalitis maintain consistent baseline levels of CSF YKL-40 throughout the course of infection.…”
Section: Biomarkers Predicting Cns Disease Progressionmentioning
confidence: 99%
“…Another marker of CSF neuronal damage is human cartilage glycoprotein 39 (YKL-40) produced by microglia following SIV infection [ 72 , 73 , 74 ]. YKL-40 is upregulated in the CSF of SIV-infected pigtailed macaques that develop encephalitis and correlates with an increase of viral load in CSF [ 74 ], while macaques that do not develop encephalitis maintain consistent baseline levels of CSF YKL-40 throughout the course of infection. Neurofilament light chain (NF-L) drastically increases in CNS during asymptomatic and chronic stages of infection in animals that develop encephalitis, and drops in animals that do not [ 70 ], showing increased neuroaxonal damage in animals that develop encephalitis.…”
Section: Biomarkers Predicting Cns Disease Progressionmentioning
confidence: 99%